The PROBLEMATIC INTERNET USE AMONG HEALTHCARE PROFESSIONALS: EMERGING BEHAVIORAL PATTERNS IN SOCIAL NETWORKING SITES ADDICTION - Sohail, Marium; Haris Rauf; Tayyeba Iftikhar Mirza; Rabia Ashfaq; Anbreen Aziz; Hasan Ibrahim (Journal of University Medical & Dental College, 2020)
ABSTRACT: BACKGROUND & OBJECTIVE: Internet has swayed all aspects of human society and the exponential rise in global internet users indicates that internet & Social Networking sites (SNS) have become an essential part of the daily lives of people with potentially addictive eﬀects of its overuse. This may lead to social isolation, depression & professional eﬀects. This behavioral addictive pattern has also been observed in increasing trend among healthcare professionals worldwide. This study aims to assess prevalence of internet addiction and its behavioral patterns (BP) in Pakistani healthcare context, to determine the prevalence and intensity of Internet Addiction (IA) among Medical Doctors. METHODOLOGY: A Quantitative; Cross-sectional Survey was conducted at Shaikh Khalifa Bin Zayed/ Azad Kashmir Combined Military Hospital Rawalakot for 2 months.After calculating sample size with 95% Conﬁdence Interval limit,100 medical and dental doctors were selected using convenience sampling. After IRB approval & informed consent data was collected using prevalidated “Young’s Internet Addiction Scale”& “Behavioral Patterns scale”. The participants recorded their response on a 5-point Likert scale and dichotomous scale for each scale respectively. Data was summarized using descriptive statistics & inferential statistics in SPSS 23. Addiction was classiﬁed into 4 categories. The signiﬁcant association between IA groups and BP groups was computed by Fisher’s exact test with P-value <0.05 as signiﬁcant. RESULTS: The Response rate was 87% with 54% males and 56% females. The prevalence of internet addiction was 79%(n=69). Out of them 36% (n=31) had mild, 41% (n=36) had moderate addiction while 2% (n=2) had severe addiction. Pattern of internet addiction symptomatology shows that prevalence of IA is higher in excessive use (87.35%) & lack of control (77.01%) while least in anticipation (35.63%) category. Statistically signiﬁcant diﬀerence was seen in behavioral patterns among addicted and nonaddicted medical and dental doctors. CONCLUSION: Internet Addiction is a recognizable disorder from the spectrum of Problematic Internet Use. This study reports the prevalence of internet addiction among health care professionals and burden of multiple behavioral patterns in association with IA, which is an emerging mental health concern.